Analisis Peran Pasar Uang dan Lembaga Keuangan dalam Menjaga Stabilitas Likuiditas Ekonomi Nasional - Bunga Aura Salsabilla; Hilmi Astuti; Indah Syaidah Muttiah; Devansyah Setiawan (Indonesia Economic Journal, 2026)
This article aims to examine the relationship between money market mechanisms and the role of financial institutions in supporting national economic stability. This research was conducted using a systematic literature review method, reviewing various scientific articles from SINTA-accredited journals and trusted sources on Google Scholar. This approach was chosen to gain a more comprehensive understanding of how the money market functions and to examine the contribution of financial institutions in supporting the economy, especially amidst constantly changing market conditions. Financial institutions play a crucial role in maintaining the smooth flow of funds, building market participant trust, and reducing the risk of liquidity imbalances that could disrupt the economic cycle. Meanwhile, the existence of an efficient money market helps maintain financial system stability, particularly in the face of current economic pressures and market uncertainty. With clear regulations and effective supervision, the money market can serve as a pillar of economic stability. This mechanism helps mitigate economic shocks and strengthens the resilience of the national economy. Ultimately, this is expected to build stronger economic independence in the future to improve public welfare.